STUDY OF THE INFLUENCE OF BIOCOMPATIBLE CONSTRUCTION MATERIALS ON INDICATORS OF ORAL FLUID OF PATIENTS WITH AN ALLERGIC STATUS DURING ORTHOPEDIC TREATMENT WITH REMOVABLE PROSTHESES - Yanishen, I.V.; Fedotova, O.L.; Savielieva, N.M.; Khlystun, N.L.; Pogorila, A.V.; Kuznetsov, R.V.; Movchan, O.V. (World of Medicine and Biology, 2022)
An analysis of the results of clinical studies showed that from 15 % to 43 % of people who are forced to use orthopedic constructions have “intolerance” of certain materials of crowns and dental prostheses. The obtained data prove the effect of structural materials on the parameters of the oral fluid of patients with an allergic status – a significant deterioration of the quality of the oral fluid was recorded due to a decrease in pH, an increase in galvanic currents and electrical conductivity already 1 day after the application of arc prostheses. The conducted research made it possible to improve the quality of orthopedic treatment of patients with an allergic status by using alternative biocompatible materials in the manufacture of removable structures of dental prostheses.
Keywords: orthopedic treatment; intolerance; allergic status; brace prostheses; glass ceramics; oral fluid